Towards de-dairyfication of the diet?—Consumers downshifting milk, yet justifying their dairy pleasures - Autio, Minna; Sekki, Sanna; Autio, Jaakko; Peltonen, Katja; Niva, Mari (Frontiers in Sustainability, 2023)
Currently, the consumption of liquid milk in Western European countries and the US is declining. At the same time, the consumption of other dairy products, including cheese and sour-milk products, is increasing. Dairy production, along with meat production, is one of the main food sources of greenhouse gases, which cause climate change. Thus, the transition toward more sustainable diets requires a reduction in the consumption of both meat and dairy products. Consumers who do not use milk (e.g., vegans) have received more scholarly attention compared to those who are reducing milk consumption. Our study focuses on Finnish consumers who have reduced the use of cow's milk but have not abandoned dairy entirely. Through qualitative data, we analyze how consumers on the one hand narrate their detachment from using milk and on the other hand justify their ongoing use of dairy products. The results show that consumers began their dietary change by first reducing meat eating, followed by milk. For the consumers, cheese eating was a source of enjoyment that was difficult to resist and to replace with plant-based alternatives, even though they were aware of the animal suffering caused by milk production. Consumers recognized the interdependence between meat and milk production and consumption, yet, at the level of everyday practices, giving up milk proved to be more challenging than giving up meat. We argue that the declining use of fluid milk contributes to the de-dairyfication of eating habits, but obstacles remain in reducing the consumption of other dairy products.